Pelatihan Produk Olahan Jamur Pasca Panen untuk Penguatan Produktivitas Ekonomi SMA Islam Al-Azhar NW Kayangan - Ismail Efendi; Safnowandi Safnowandi; Ika Nurani Dewi; Septiana Dwi Utami; Zainal Abidin (Jurnal Pengabdian UNDIKMA, 2020)
This service activity aims to provide alternative post-harvest handling of mushrooms, especially Oyster Mushrooms that are able to produce products that are acceptable to consumers; provide an alternative to consumers of products made from oyster mushrooms, and have a long shelf life and open up opportunities for the development of agribusiness-based home industries. The activity method is carried out by lecturing and discussing the characteristics of Oyster Mushrooms and their post-harvest handling; production of products as well as testing of product acceptance by the community; and the development of home industries with pricing and packaging and licensing of small industries. The targets of this community service activity are teachers and students / students at the Al-Azhar NW Kayangan Islamic High School, Sandik Village, Batu Layar District, West Lombok Regency. The results of this community service activity show that the teachers and students are very enthusiastic and feel the enormous benefits of this activity. It is hoped that this activity can be increased again by still paying attention to the needs of teachers and students for sustainable entrepreneurship so that it can help the school economy to innovate in creating various sources of school income. The activity was greeted with high enthusiasm, because almost all partner schools had no object to increase the economic productivity of their schools. The teachers really hope that the next activity can be continued with other food processing materials with a longer duration.